2022
DOI: 10.1007/s13318-022-00763-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Correction Factors to Enable Assessment of Clinical Risk from In Vitro CYP3A4 Induction Data and Basic Drug-Drug Interaction Models

Abstract: Background and Objective Induction of drug-metabolizing enzymes can lead to drug-drug interactions (DDIs); therefore, early assessment is often conducted. Previous reports focused on true positive cytochrome P450 3A (CYP3A) inducers leaving a gap in translation for in vitro inducers which do not manifest in clinical induction. The goal herein was to expand the in vitro induction dataset by including true negative clinical inducers to identify a correction factor to basic DDI models, which reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…IVIVE of DDIs caused by induction is typically adjusted with correction factors or by correlation methods, especially for CYP3A4 33,34,42 . Such methods are needed because of a pronounced variability in the in vitro estimation of CYP3A4 induction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IVIVE of DDIs caused by induction is typically adjusted with correction factors or by correlation methods, especially for CYP3A4 33,34,42 . Such methods are needed because of a pronounced variability in the in vitro estimation of CYP3A4 induction.…”
Section: Discussionmentioning
confidence: 99%
“…14 IVIVE of DDIs caused by induction is typically adjusted with correction factors or by correlation methods, especially for CYP3A4. 33,34,42 Such methods are needed because of a pronounced variability in the in vitro estimation of CYP3A4 induction. This is likely not related to interindividual variability but rather to the weak performance of 2D culture format of PHHs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, one possible reason for the inaccurate predictions of the new equation is inaccuracy in the estimated inducer drug concentration in the enterocytes. Recently, a study demonstrated that using unbound average hepatic inlet concentration as the input for gut concentration leads to better predictions of DDIs 44 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study demonstrated that using unbound average hepatic inlet concentration as the input for gut concentration leads to better predictions of DDIs. 44 Further work is needed to extend the applicability of our approach. First, we have only collected CYP3A4-related interaction pairs of inducers and substrates to evaluate the prediction accuracy.…”
Section: Articlementioning
confidence: 99%